2002
DOI: 10.5713/ajas.2002.844
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Evaluation of Some Fodder Tree Species during the Dry Season in Central Sudan

Abstract: The potential nutritive value was studied on leaves of seven fodder trees in Central Sudan during dry season at two distinct periods, the early dry and the late. The chemical composition, mineral concentration, in vitro organic matter digestibility (IVOMD), in situ OM or nitrogen degradability and estimated metabolizable energy showed a wide variation among fodder tree species and between different periods of the dry season. Crude protein (CP) ranged from 285 to 197 g/kg DM at early dry season, with a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
5
9
0
1
Order By: Relevance
“…Shayo and Uden (1999) and Abdulrazak et al (2000) also reported high phenolic and tannin levels in some East African browses. High polyphenolic components were also reported in semi-arid of north Egypt (Salem, 2005) and arid regions of Sudan (Fadel Elseed et al, 2002). There were differences between levels of TP and CT in the tree foliages studied compared to similar tree foliages reported by others (e.g., Rubanza et al (2003) reported TP and CT were between 65-237 and 6-74 g/kg DM, respectively).…”
Section: Composition Of the Tree Foliagessupporting
confidence: 61%
“…Shayo and Uden (1999) and Abdulrazak et al (2000) also reported high phenolic and tannin levels in some East African browses. High polyphenolic components were also reported in semi-arid of north Egypt (Salem, 2005) and arid regions of Sudan (Fadel Elseed et al, 2002). There were differences between levels of TP and CT in the tree foliages studied compared to similar tree foliages reported by others (e.g., Rubanza et al (2003) reported TP and CT were between 65-237 and 6-74 g/kg DM, respectively).…”
Section: Composition Of the Tree Foliagessupporting
confidence: 61%
“…We do not have any logical explanation as to why Dorcas gazelles used B. aegyptiaca trees less than Acacia trees. Gazelles used Tamarix trees the least, which is not surprising given that Tamarix are believed to be the poorest forage of the three species (El-Beheiry and El-Kady, 1998;El Seed et al, 2002;Araya et al, 2003). Although T. aphylla and T. nilotica are considered trees, in the Wadi Gemal National Park both species have a shrub-like morphology, and are therefore less likely to be used as territorial landmarks.…”
Section: Discussionmentioning
confidence: 88%
“…Ce rapport est cependant inferieur à celui obtenu par Kabore-Zoungrana et al (2008) chez B aegyptiaca (18). Lorsque ce rapport est élevé, il interfère avec l'utilisation efficiente du Ca par les animaux même si les feuilles contiennent un niveau approprié en Ca (Fadel Elseed et al, 2002).…”
Section: Discussionunclassified